Compaction of urea 46% nitrogen by uniaxial die compaction - Shamsudin, Intan Soraya; Anuar, Mohd Shamsul; Yusof, Yus Aniza; Mohd Hanif, Ahmad Husni; Mohd Tahir, Suraya (Faculty of Engineering, Universiti Putra Malaysia, 2012)
The compaction process of urea 46% nitrogen fertilizer in powder and granular form using uniaxial die compaction technique could be characterized by evaluating their compressibility, compactibility and tabletability characteristics. The results were analyzed in terms of the porosity, compaction pressure, tensile strength and disintegration. Results demonstrated that the urea powder tablet significantly became more compressible at 150.7 MPa and 188.3 MPa than the granule tablet. The compactability result shows that the powder tablet has strong bonding and thus, it has higher tensile strength in comparison to the urea granule tablet. For the quality assessment of the tablets, it was observed that powder tablet has significantly low disintegration rate than granule tablet only at compaction pressure of 150.7 MPa. Indeed, it can be conclude that compaction of urea fertilizer in granule and powder form needs further improvement with special focus on the disintegration and dissolution characteristics.